Developmental stage and pulsing in inflorescences of torch ginger - Carneiro, Daniella Nogueira Moraes; Paiva, Patrícia Duarte de Oliveira; Carneiro, Leandro Flávio; Rodrigues, Roseane de Souza; Lima, Luiz carlos de Oliveira; Dias, Gabrielen de Maria Gomes; Pedroso, Rodolfo Guimarães Alexandre Vasques (Ornamental Horticulture, 2014)
Tropical species are very important in the flower market, but information in harvest and postharvest procedures are not enough. There is not enough information on pulsing or holding solutions for most tropical species. The objective was to evaluate the durability and quality of postharvest torch ginger flower stems (Etlingera elatior) at sucrose concentrations in pulsing solution and different flower opening stages. Flower stems were harvested early morning at three flower opening stages: inflorescences with 1/3, 2/3 and completely open bracts, withal the stalks were pulsed with sucrose solution at concentrations of 0 (control), 10, 20, and 30% for 24h. Experimental design was completely randomized in a 4x3x6 factorial with 3 replications in a split plot in time. Evaluations were performed every 3 days, determining the fresh weight of flowers and assessing inflorescence quality through scores on a 0-4 point scale. Commercial vase life of stalks is longer (10 days) when inflorescences are harvested with 1/3 bracts opened. It is recommended to carry out pulsing in torch ginger flower stems with concentration of 20% sucrose for 24h for inflorescences harvested with 1/3 or 2/3 of the bracts opened.